관절염 환자를 위한 타이치 프로그램 적용 후 통증, 피로, 인지된 건강상태, 관절뻣뻣함, 일상활동장애, 우울의 변화 - 이경숙(Lee Kyung-Sook); 소애영(So Aeyoung); 최정숙(Choi Jung Sook); 이은희(Lee Eun Hee); 유보비(Yoo Bo BI) (근관절건강학회지, 2008)
Purpose: The purpose of this study was to observe the changes of the pain, fatigue, perceived health status, disability in ADL, and depression after Tai Chi for arthritis. Method: The subjects were 19 osteoarthritis women enrolled at one primary health care post. They have agreed to participate in this study, and participated in the 12-week Tai Chi program from Dec. 2006 to Mar. 2007, and all the measurement processes in right after, 2 months later, and 4 months later after Tai Chi program. The measurement tools of this study were all self-reported questionnaires such as Numerical Rating Scale (0-100) for pain, fatigue, and perceived health status, Korean-WOMAC (Western Ontario and McMaster University Osteoarthritis) Index for joint stiffness, Korean Health Assessment Questionnaire, and CES-Depression scale. Results: The repeated measure ANOVA revealed the significant differences on pain among the right after, 2 months later, and 4 months later the program. Especially 2 months later after program, pain was significantly increased than right after by t-test. There were no significant differences on fatigue, perceived health status, disability in ADL, and depression. Conclusion: Pain was increased after Tai Chi for arthritis program, but fatigue, perceived health status, disability in ADL, and depression were not changed until 4 months after Tai Chi program.